Ukraine in the European Union’s partnership policy: a case of institutionalized ambiguity - Ferreira-Pereira, Laura C. (2015)
The relations between the European Union (EU) and Ukraine have been predominantly explained in the light of the European Neighbourhood Policy that ascribes a central role to political conditionality. This analytical approach, however, overlooks the fact that since the 1990s, the EU has been developing a partnership policy that needs to be taken into consideration. This partnership policy was enshrined in the Partnership and Cooperation Agreement and the EU Common Strategy towards Ukraine in 1999, and with the advent of the twenty-first century came to incorporate differentiated elements, notably the growing politico-diplomatic alignment within the realm of Common Foreign and Security Policy and a tangible participation in Common Security and Defence Policy missions. While these features have ascribed the country a distinctive status, neither of the parties has hitherto engaged in formalizing a strategic partnership. Against this backdrop, this article attempts to explain this somewhat paradoxical situation by teasing out and discussing the evolution of the cooperation between the EU and Ukraine which is informed by a complex institutional and legal design. It argues that two decades of bilateral relationship have engendered an ambiguous partnership, given the necessity felt by the EU to give the upper hand to an intergovernmentally driven ‘Russia-first policy’, while accommodating Kiev's ambitions to become a EU full-fledged member.